THE IMPACT OF FUEL OIL INCREASE ON STOCK PRICES: AN EVENT STUDY APPROACH ON THE IDX80 INDONESIA STOCK EXCHANGE 2022 - Ricky Bryan Tampubolon; Simon Nisja Putra Zai; Hani Agustin (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
The objective of this study is to analyze the different responses of the market when fuel price hikes are announced in Indonesia. Utilizing an event study approach, abnormal returns, trading volume activity, and bid-ask spread differentials were measured during a 9-day period before and after the announcement. The research was conducted during the transition from the pandemic phase to the endemic phase of Covid-19. This study is significant in understanding the impact of fuel price announcement as a disruptive factor in the national economic recovery during the post-pandemic period. The sample consisted of IDX80 companies, and the Wilcoxon statistical test was employed for analysis. According to the results, there is no notable disparity in abnormal returns prior to and following the announcement of fuel price increases. However, the increase in fuel prices had a significant impact on trading volume activity before and after the event, as well as differences in bid-ask spread among IDX80 companies. These results suggest market uncertainty, influencing investor behavior and risk management strategies by companies to prevent losses. This research provides new insights into the relationship between economic events and the capital market, offering valuable information for market participants, investors, and policymakers in making informed investment decisions.